2001
DOI: 10.1002/eat.1106
|View full text |Cite
|
Sign up to set email alerts
|

Parental influences on eating behavior in obese and nonobese preadolescents

Abstract: Such an eating style can be hypothesized to explain an increased calorie intake in obese children, promoting a positive energy balance in the long term. The data support a learning model of obesity in childhood, which also has implications for family treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 14 publications
4
31
0
1
Order By: Relevance
“…In support, one observational study has found that higher eating rate in 3-5 year olds is associated with more maternal prompts to eat (66) . The theory is also consistent with the finding that overweight children eat faster only when their mothers are present in the laboratory (22) . Food-cue responsiveness.…”
Section: Parental Influences On Appetitive Traitssupporting
confidence: 87%
See 1 more Smart Citation
“…In support, one observational study has found that higher eating rate in 3-5 year olds is associated with more maternal prompts to eat (66) . The theory is also consistent with the finding that overweight children eat faster only when their mothers are present in the laboratory (22) . Food-cue responsiveness.…”
Section: Parental Influences On Appetitive Traitssupporting
confidence: 87%
“…Obesenormal differences in average eating rate were not found to be significant in this study (n 40), but evidence for a trend towards faster eating emerged in the obese group (21) . Eating rate may also be influenced by the eating situation and choice of meal; in a repeated-measures study (n 80) using computerised monitoring of a standard yoghurt meal overweight children were reported to display a faster eating rate only when their mothers were present in the laboratory (22) . In a large sample (n 252) of 9-12-year-old twins participating in a cohort study of eating behaviour, physical activity and adiposity, eating rate has been examined across the weight distribution.…”
Section: Satiety Responsiveness and Child Obesitymentioning
confidence: 99%
“…However, it may be relevant that obese children eat relatively faster and with larger bites, and they accelerate their eating rate toward the end of the meal, but only in the presence of a parent. 55 Other findings from this study also warrant discussion. We found evidence that the effects of cueing on desire to eat and prospective portion size are not specific to the cued food (pizza).…”
Section: Discussionmentioning
confidence: 65%
“…Previous research examining the effects of others on children's eating behavior has focused on the influence of parents on children's food consumption (e.g., Faith et al, 2004;Klesges et al, 1983;Koivisto et al, 1994;Laessle et al, 2001) and on the effects of different models on children's acceptance of new foods (Addessi et al, 2005;Birch, 1980;Duncker, 1938;Harper & Sanders, 1975;Hendy, 2002;Hendy & Raudenbush, 2000). However, these studies did not specifically examine the impact of familiarity on children's food consumption, and it is not clear from these studies how the relationship with co-eaters influences modeling of eating in children.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have looked at the influence of parents on children's food consumption (e.g., Faith, Scanlon, Birch, Francis, & Sherry, 2004;Klesges, Coates, Brown, Sturgeon-Tillisch, Moldenhauer-Klesges, Holzer, Woolfrey, & Vollmer, 1983;Koivisto, Fellenius, & Sjoden, 1994;Laessle, Uhl, & Lindel, 2001), few experimental studies have tested the influence of peers on children's food intake. In fact most of the research in children has focused on the effects of others on children's acceptance of unfamiliar foods (Addessi, Galloway, Visalberghi, & Birch, 2005;Birch, 1980;Duncker, 1938;Harper & Sanders, 1975;Hendy, 2002;Hendy & Raudenbush, 2000).…”
Section: Introductionmentioning
confidence: 99%